Polyurethane composite coating based on active and passive protection structures and preparation method thereof

By esterification and modification of GO nanosheets and combining with polyurethane matrix, a high-performance friction-reduction and anti-corrosion coating is formed, which solves the problem of metal materials damaged by corrosion and wear in the marine environment, and realizes that the coating is under harsh environments High corrosion resistance and low wear performance.

CN119410252AActive Publication Date: 2025-02-11LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411734476.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-11
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Metal materials in the marine environment are damaged due to the interaction between corrosion and wear, making it difficult for marine equipment to serve for a long life under harsh environments, and existing coatings are difficult to have both lubricating and anti-corrosion functions.

Method used

Using a polyurethane composite coating based on active and passive protection structure, the GO nanosheets are esterified and modified to enhance their dispersion stability and interface compatibility, and combined with isophorone diisocyanate and polyether polyol to form a high Performance friction-reducing and anti-corrosion coating.

Benefits of technology

It significantly improves the corrosion resistance and friction reduction performance of the coating, extends the permeability path of corrosive media, and reduces wear rate. It is suitable for offshore equipment in marine environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410252A_ABST
    Figure CN119410252A_ABST
Patent Text Reader

Abstract

The invention discloses a polyurethane composite coating based on an active and passive protection structure and a preparation method of the polyurethane composite coating, and relates to the technical field of functional antifriction and corrosion prevention. The polyurethane composite coating provided by the invention is obtained by mixing active and passive protection structure GO nanosheets, isophorone diisocyanate, polyether polyol, toluene and N, N-dimethylformamide according to a certain proportion, spraying the mixture on the surface of a base material and curing. Wherein the active and passive protection structure GO nanosheet is a GO nanosheet grafted with hydroxyl benzothiazyl disulfide. The polyurethane composite coating provided by the invention has remarkable antifriction effect and corrosion resistance, and has potential application value in the field of marine corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of friction reduction and anti-corrosion, and in particular to a polyurethane composite coating based on an active and passive protective structure and a preparation method thereof. Background Art

[0002] In the marine environment, metal materials are damaged and fail due to the interaction of seawater corrosion and wear, which seriously restricts the development of the marine industry. my country is actively promoting the development and utilization of marine energy by building offshore wind farms and using tidal energy to generate electricity. my country's independently developed high-end equipment has been installed in offshore areas and has entered the large-scale service stage. However, these marine equipment have been immersed in seawater for a long time, causing serious corrosion of metal materials exposed to the marine atmosphere. At the same time, the operation of marine equipment is often accompanied by various friction and wear problems, which leads to wear and damage of equipment, thereby accelerating the damage and failure of metal materials, which has become a bottleneck problem restricting the efficient, stable and long-life service of modern marine equipment. The current marine equipment materials (such as titanium alloys, copper alloys and nickel alloys, etc.) cannot fully meet the long-life operation requirements of the rotating system or other components of marine engineering equipment that are exposed to the marine environment for a long time. Therefore, how to solve the problem of component failure caused by corrosion and wear faced by the rotating system, anchor chain or other components in the marine environment is a technical problem that needs to be solved urgently in the field of marine equipment. Therefore, innovation and research are needed in material selection, surface treatment and coating technology to improve the corrosion resistance and friction reduction performance of equipment components.

[0003] Polyurethane is often used as a topcoat for marine coatings due to its wear resistance, weather resistance, corrosion resistance, chemical stability, adhesion, and controllable soft and hard segments. In view of the presence of strong polar groups in polyurethane molecules, such as urea, carbamate, amide, and other groups containing high surface energy, these molecules will accumulate heat under cyclic alternating stress and further destroy the cross-linked structure of the polymer, resulting in a higher friction coefficient of the polyurethane coating during friction and causing more serious corrosion and wear. In order to meet the requirements of high reliability and long life of polyurethane coatings in marine environments, composite functional fillers such as GO can be added as anti-friction and anti-corrosion fillers to provide excellent anti-friction and corrosion resistance properties of the coating. However, the van der Waals force between GO sheets is large, and it is easy to agglomerate, and even cause local defects in the resin to affect its performance. Therefore, before GO nanosheets are filled into the polyurethane matrix, in order to improve the interfacial compatibility between it and the polymer and prevent agglomeration from affecting the dispersibility, it is necessary to modify its surface to make it environmentally adaptable.

[0004] In summary, based on the concept of synergistic chemical and physical effects and unified friction reduction and anti-corrosion functions, the present invention intends to provide a special nanostructure that combines active chemical corrosion inhibition with passive physical barrier defense, and a synergistic combination of functional components, to break through the bottleneck that existing lubricating coatings are difficult to have both lubrication and anti-corrosion functions under harsh working conditions, and obtain a high-performance, long-life, integrated coating with friction reduction and corrosion resistance to meet the use requirements of marine engineering equipment in harsh environments. Summary of the invention

[0005] The purpose of the present invention is to provide a polyurethane composite coating based on an active and passive protective structure and a preparation method thereof, in order to improve the friction reduction and anti-corrosion effects of materials in environments such as the ocean.

[0006] In order to achieve the above-mentioned purpose, the present invention provides a polyurethane composite coating based on an active and passive protective structure, which comprises the following raw materials by mass: 0.01 to 0.1 parts of GO nanosheets of the active and passive protective structure, 5 to 10 parts of isophorone diisocyanate, 5 to 10 parts of polyether polyol and 20 to 40 parts of solvent; wherein the GO nanosheets of the active and passive protective structure are GO nanosheets grafted with hydroxybenzothiazole disulfide.

[0007] Preferably, the hydroxybenzothiazole disulfide is self-made, and its preparation process is as follows:

[0008] (1) 0.01-0.1 mol of dibenzothiazole disulfide and 500-100 mL of chloroform are mixed, and then 0.01-0.1 mol of β-mercaptoethanol is added dropwise, and the mixture is reacted under stirring conditions. The reaction temperature of the stirring reaction is 20-30° C. and the stirring time is 3-4 hours;

[0009] (2) After the reaction, hydroxybenzothiazole disulfide is obtained, extracted with a 3-5% by mass NaOH aqueous solution and deionized water, dried with Na2SO4 and filtered, and then purified by recrystallization with n-hexane after rotary evaporation to obtain the treated hydroxybenzothiazole disulfide.

[0010] Preferably, the above-mentioned polyurethane composite coating comprises the following raw materials by weight: 0.02-0.06 parts of active and passive protective structure GO nanosheets, 6-9 parts of isophorone diisocyanate, 8-10 parts of polyether polyol and 28-32 parts of solvent.

[0011] Preferably, the method for preparing the active and passive protective structure GO nanosheets comprises the following steps:

[0012] (1) mixing GO nanosheets and N,N-dimethylformamide and performing ultrasound to obtain a GO nanosheet mixed solution;

[0013] (2) The obtained GO nanosheet mixed solution is mixed with hydroxybenzothiazole disulfide and N,N-dimethylformamide, stirred, and then centrifuged, washed and dried to obtain GO nanosheets with active and passive protective structures.

[0014] Preferably, in the above step (1), the dosage ratio of GO nanosheets to N,N-dimethylformamide is 0.5-1 g: 100-300 mL, and the ultrasonication time is 30-40 min.

[0015] Preferably, the obtained GO nanosheet mixed solution is mixed with hydroxybenzothiazole disulfide and N,N-dimethylformamide, wherein the amount ratio of hydroxybenzothiazole disulfide and N,N-dimethylformamide is 0.5-1g:100-300mL; it is carried out under stirring conditions, the stirring temperature is preferably 55-65°C, the stirring speed is 200-300rpm, and the stirring time is 5-6h; centrifugation is centrifugal separation at 8000rpm for 10min; washing is alternating washing with ethanol and deionized water.

[0016] Preferably, the polyether polyol in the above-mentioned polyurethane composite coating is one or more of NX9005, NX9006 or NX9007; the solvent therein is a mixture of toluene and N,N-dimethylformamide, and the mass ratio thereof is 1-2g:1g.

[0017] The present invention also provides a method for preparing the polyurethane composite coating, comprising the following steps:

[0018] (1) mixing active and passive protection structure GO nanosheets, isophorone diisocyanate and a solvent to obtain a mixed slurry;

[0019] (2) adding polyether polyol to the obtained mixed slurry to obtain a polyurethane composite slurry;

[0020] (3) Spraying the obtained polyurethane composite slurry on the surface of the substrate and curing it to obtain a polyurethane composite coating with anti-friction and anti-corrosion properties.

[0021] The present invention has the following advantages:

[0022] 1) The present invention esterifies GO by MBTS2OH to enhance the dispersion stability of GO in the coating and the interfacial compatibility with the polyurethane adhesive. The flaky structure of GO and the "maze effect" formed by stacking in the coating can extend the penetration path of the corrosive medium, and the cleavage of the disulfide bond in MBTS2OH can release the corrosion inhibitor, thereby improving the corrosion resistance of the coating in the marine environment.

[0023] 2) The coating of the present invention uses polyurethane as a base material, which has chemical stability, adhesion and controllable soft and hard segments. The present invention uses surface-modified GO as a wear-resistant and anti-corrosion filler, which not only has excellent lubrication properties but also has excellent corrosion resistance, thus significantly improving the corrosion resistance and friction reduction properties of the coating.

[0024] 3) The marine anti-friction and anti-corrosion functional integrated coating of the present invention introduces anti-friction and anti-corrosion fillers, so that the coating has both excellent anti-friction and anti-corrosion functions. Under dry friction conditions, the coating exhibits good tribological properties. The coating improves the anti-corrosion and anti-friction performance of the organic bonding coating exposed to the marine environment for a long time, and reduces the damage and failure problems caused by factors such as high load impact and mechanical wear. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a physical picture of the anti-friction and anti-corrosion coating obtained in Example 1 of the present invention.

[0026] Figure 2 The tribological properties of the anti-friction and anti-corrosion coatings obtained in the comparative examples and embodiments of the present invention are measured. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Note: The experimental methods in the following examples are conventional methods unless otherwise specified, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified.

[0029] The invention provides a polyurethane composite coating based on an active and passive protective structure, which comprises the following preparation raw materials, measured by weight: 0.01 to 0.1 parts of active and passive protective GO nanosheets, 5 to 10 parts of isophorone diisocyanate, 5 to 10 parts of polyether polyols and 20 to 40 parts of solvents; wherein the active and passive protective structure GO nanosheets are GO nanosheets grafted with hydroxybenzothiazole disulfide.

[0030] The preparation method of the active and passive protection structure GO nanosheet is as follows:

[0031] (1) first mixing GO nanosheets and N,N-dimethylformamide, and obtaining a GO nanosheet mixed solution after ultrasonication;

[0032] (2) secondly mixing the GO nanosheet mixed solution, hydroxybenzothiazole disulfide and N,N-dimethylformamide, and modifying them to obtain GO nanosheets with active and passive protective structures;

[0033] Among them, GO nanosheets are preferably single-layer GO nanosheets with a thickness of preferably 1 nm. The usage ratio of GO nanosheets to N,N-dimethylformamide is (0.5-1) g: (100-300) mL, the preferred ratio is 0.8 g: 100-300 mL, more preferably 0.8 g: 150-200 mL, and most preferably 0.8 g: 200 mL; the first ultrasound after mixing, the ultrasound time is 30-40 min, preferably 30-35 min, and most preferably 30 min.

[0034] The obtained GO nanosheet mixed solution is secondly mixed with hydroxybenzothiazole disulfide and N,N-dimethylformamide, and the dosage ratio of hydroxybenzothiazole disulfide and N,N-dimethylformamide is (0.5-1) g: (100-300) mL, more preferably (0.5-0.8) g: (200-300) mL, and most preferably 0.6 g: 200 mL.

[0035] The process is carried out under stirring, with a stirring temperature of preferably 55-65°C, more preferably 60-65°C, and most preferably 60°C; the stirring temperature is preferably achieved by heating in an oil bath; the stirring speed is preferably 200-300rpm, more preferably 250-300rpm, and most preferably 250rpmn; the stirring time is preferably 5-6h, more preferably 5.5-6h, and most preferably 6h.

[0036] The hydroxybenzothiazole disulfide used in the preparation process of the active and passive protection structure GO nanosheet is self-made, and the specific preparation process is as follows:

[0037] (1) Dibenzothiazole disulfide and chloroform are mixed, and then β-mercaptoethanol is added dropwise to react under stirring conditions, wherein the amount ratio of dibenzothiazole disulfide, chloroform and β-mercaptoethanol is preferably (0.01-0.1) moL: (500-100) mL: (0.01-0.1) moL, more preferably (0.02-0.08) moL: (800-1000) mL: (0.02-0.08) moL, and most preferably 0.05 moL: 800 mL: 0.05 moL; the reaction temperature of the stirring reaction is preferably 20-30°C, more preferably 25-30°C, and most preferably 25°C; the rotation speed is preferably 200-300 rpm, and more preferably 250 rpmn; the stirring time is preferably 3-4 h, more preferably 3.5-4 h, and most preferably 4 h.

[0038] (2) after the reaction, hydroxybenzothiazole disulfide is obtained, which is then extracted with an aqueous NaOH solution and deionized water, dried with Na2SO4 and filtered, and then purified by recrystallization with n-hexane after rotary evaporation to obtain the treated hydroxybenzothiazole disulfide;

[0039] The mass fraction of the NaOH aqueous solution is preferably 3-5%, more preferably 4-5%, most preferably 5%; the number of extractions is preferably 4-6 times, more preferably 5-6 times, most preferably 6 times; the rotary evaporation temperature is 50-70°C, more preferably 50-60°C, most preferably 60°C; after the synthesis of hydroxybenzothiazole disulfide, it is preferably subjected to vacuum drying at a temperature of 50-70°C, more preferably 60-70°C, most preferably 70°C; the vacuum drying time is preferably 10-15h, more preferably 12-15h, most preferably 12h.

[0040] Calculated by weight, the polyurethane composite coating provided by the present invention contains 0.01 to 0.1 parts of active and passive protective structure GO nanosheets, preferably 0.02 to 0.08 parts, and more preferably 0.02 to 0.06 parts.

[0041] Calculated by weight, the polyurethane composite coating provided by the present invention contains 5 to 10 parts of isophorone diisocyanate, preferably 6 to 10 parts, and more preferably 6 to 9 parts.

[0042] The polyurethane composite coating provided by the present invention comprises 5 to 10 parts of polyether polyol, preferably 6 to 10 parts, and more preferably 8 to 10 parts, by weight; wherein the polyether polyol is preferably one or more of NX9005, NX9006 or NX9007.

[0043] In terms of parts by mass, the polyurethane composite coating provided by the present invention contains 20 to 40 parts of a solvent, preferably 25 to 35 parts, and more preferably 28 to 32 parts; the solvent is preferably a mixed solvent of toluene and N,N-dimethylformamide, and the mass ratio of toluene to N,N-dimethylformamide in the mixed solvent is 5 to 3:1, preferably 4:1, and more preferably 3:1.

[0044] The present invention also provides a more optimal method for preparing active and passive protective GO nanosheets, which is as follows:

[0045] 0.05 mol of dibenzothiazole disulfide (BSSB) was dissolved in 800 mL of chloroform (CHCl3), and 3.91 g of β-mercaptoethanol was slowly added dropwise, followed by stirring at 25°C for 4 h to obtain a mixed solution; the mixed solution was first extracted 6 times with a 5 wt% NaOH aqueous solution, then extracted 6 times with deionized water, and then dried with Na2SO4, and finally filtered and rotary evaporated at 60°C to obtain hydroxybenzothiazole disulfide; the hydroxybenzothiazole disulfide was purified by recrystallization with n-hexane, and white needle-shaped crystals were collected, recorded as MBTS2OH, and then vacuum dried at 70°C for 12 h;

[0046] On the one hand, 0.6 g of hydroxybenzothiazole disulfide and 200 mL of N,N-dimethylformamide (DMF) were added to a three-necked flask and uniformly dispersed; on the other hand, 0.8 g of GO nanosheets were dispersed in 200 mL of DMF, ultrasonically dispersed for 30 minutes, and then poured into a three-necked flask and stirred in a 60°C oil bath for 6 hours; the reaction mixture was centrifuged with a centrifuge at a speed of 8000 rpm for 10 minutes, and the obtained suspension was alternately washed with ethanol and deionized water to obtain GO modified with MBTS2OH (MBTS2GO), which was placed in a freeze dryer and dried for 12 hours to obtain GO nanosheets with active and passive protective structures.

[0047] The present invention also provides a method for preparing a polyurethane composite coating based on an active and passive protective structure, comprising the following steps:

[0048] (1) mixing active and passive protection structure GO nanosheets, isophorone diisocyanate, polyether polyol and solvent to obtain a mixed slurry;

[0049] (2) Spraying the obtained mixed slurry on the surface of the substrate and curing it to obtain a polyurethane composite coating with integrated anti-friction and anti-corrosion functions.

[0050] Among them, it is preferred to first mix the active and passive protection structure GO nanosheets and the solvent with isophorone diisocyanate for the first time to obtain a mixed solution; and then mix the mixed solution with polyether polyol for the second time to obtain a mixed slurry. The first mixing is preferably carried out under stirring conditions, and the stirring speed is preferably 300-400rpm, more preferably 320-380rpm, and most preferably 350rpm; the stirring time is preferably 1-4h, more preferably 2-4h, and most preferably 2h.

[0051] The second mixing is preferably carried out under stirring conditions, the stirring speed is preferably 300-400 rpm, more preferably 320-380 rpm, most preferably 350 rpm; the stirring time is preferably 2-6 h, more preferably 2-4 h, most preferably 4 h.

[0052] Among them, the substrate is preferably a substrate treated according to the national standard GB / T8923.1; the spraying conditions are preferably: the distance between the mixed slurry and the substrate surface is preferably 20 to 25 cm, more preferably 21 to 24 cm, and most preferably 22 to 23 cm; the spraying is preferably carried out in compressed air of 0.15 to 0.20 MPa; the thickness of the coating after spraying is preferably 30 to 50 μm, more preferably 35 to 45 μm, and most preferably 38 to 40 μm.

[0053] The curing temperature is preferably programmed temperature curing, and the curing temperature and time are preferably 120° C. for 2 hours, and then heated to 150° C. for 4 hours.

[0054] The polyurethane composite coating provided by the invention has both friction reduction and anti-corrosion functions, and has potential application value in the field of marine anti-corrosion.

[0055] Example 1

[0056] This embodiment provides a method for preparing a polyurethane composite coating, which includes raw materials by weight: 0.05 parts of active and passive protective structure GO nanosheets (MBTS2GO), 8.8 parts of isophorone diisocyanate (IPDI), 10 parts of polyether polyol (specific type is NX9005), 20 parts of toluene, and 10 parts of N,N-dimethylformamide. The preparation process is as follows:

[0057] MBTS2GO and isophorone diisocyanate were added to a mixed system of toluene and N,N-dimethylformamide, and stirred (at a speed of 350 rpm for 2 h), and then polyether polyol was added dropwise, and stirred in a nitrogen atmosphere at 70°C (at a speed of 350 rpm for 4 h) to obtain a polyurethane (PU) composite slurry;

[0058] The obtained polyurethane composite slurry was sprayed on the surface of the substrate (Q235 steel) treated according to the national standard GB / T8923.1, cured at 120°C for 4 hours, and then heated to 150°C for 2 hours to obtain an integrated polyurethane composite coating (MBTS2GO / PU) with anti-friction and anti-corrosion functions. The actual appearance is as follows: Figure 1 shown.

[0059] Comparative Example 1

[0060] This comparative example provides an integrated coating with anti-friction and anti-corrosion functions, and the raw materials for preparation include (by mass): 8.8 parts of isophorone diisocyanate (IPDI), 10 parts of polyether polyol (specific type is NX9005), 20 parts of toluene, and 10 parts of N,N-dimethylformamide. The preparation process is as follows:

[0061] First, isophorone diisocyanate, toluene and N,N-dimethylformamide were mixed, and then polyether polyol was dropped, and stirred in a nitrogen atmosphere at 70°C (speed of 350 rpm, time of 4 hours) to obtain a polyurethane (PU) slurry;

[0062] The obtained polyurethane slurry was sprayed on the surface of the substrate (Q235 steel) treated according to the national standard GB / T8923.1, cured at 120°C for 4 hours, and then heated to 150°C for 2 hours to obtain an integrated coating (PU) with anti-friction and anti-corrosion functions.

[0063] Comparative Example 2

[0064] This comparative example provides an integrated coating with anti-friction and anti-corrosion functions, and the raw materials for its preparation include (by mass): 0.05 parts of GO nanosheets, 8.8 parts of isophorone diisocyanate (IPDI), 10 parts of polyether polyol (specifically NX9005), 20 parts of toluene, and 10 parts of N,N-dimethylformamide.

[0065] First, GO and isophorone diisocyanate were added to a mixture of toluene and N,N-dimethylformamide and stirred (at a speed of 350 rpm for 2 h). Then polyether polyol was added dropwise and stirred in a nitrogen atmosphere at 70 °C (at a speed of 350 rpm for 4 h) to obtain a polyurethane (PU) composite slurry.

[0066] The obtained polyurethane composite slurry was sprayed on the surface of the substrate (Q235 steel) treated according to the national standard GB / T8923.1, cured at 120°C for 4 hours, and then heated to 150°C for 2 hours to obtain an integrated coating (GO / PU) with anti-friction and anti-corrosion functions.

[0067] The tribological properties of the coatings obtained in Example 1, Comparative Example 1 and Comparative Example 2 were measured. The test methods and performance data used are shown in Table 1. All substrates are Q235 steel substrates. In order to avoid accidental errors, two sets of data are provided for the determination of the friction coefficient and the coating wear rate in Table 1. The test results are shown in Table 1. Figure 2 As shown, Figure 2 a in the figure is the friction curve of the three coatings under the conditions of 5N load, 5Hz frequency and sliding distance of 100m; Figure 2 b in the figure is the average friction coefficient and wear rate of the three coatings under the conditions of 5N load, 5Hz frequency and sliding distance of 100m. Figure 2 The friction and wear behavior of polyurethane-based composite coatings is shown. It can be seen that the friction coefficients of GO / PU and MBTS2GO / PU composite coatings are 0.26 and 0.22, respectively, which are lower than those of pure PU coating (0.52). The wear rate of polyurethane composite coatings was further studied under dry friction conditions. Figure 2As shown in b, the wear rate of pure PU coating is 5.5×10 -5 mm 3 ·N -1 ·m -1 However, when graphene nanosheets were added as reinforcement, the wear rate of the coatings decreased. In particular, the wear rate of the MBTS2GO / PU composite coating was low, only 3.14×10 -5 mm 3 ·N -1 ·m -1 Compared with GO / PU composite coating and PU coating, MBTS2GO / PU composite coating has better tribological properties.

[0068] Table 1 Detection methods and performance data of the coatings obtained in Example 1 and Comparative Examples 1-2

[0069]

[0070] It can be seen from Table 1 that the anti-friction and anti-corrosion function integrated polyurethane composite coating provided by the present invention has a low friction coefficient and excellent corrosion resistance on the surface of a low-carbon steel substrate, and can be exposed to a marine environment for long-term use. It can be seen that the polyurethane composite coating can be widely used in the friction reduction, salt resistance and corrosion protection of marine materials, and has application potential in the field of marine corrosion protection.

[0071] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A polyurethane composite coating based on an active and passive protective structure, characterized in that: The coating comprises the following raw materials by weight: 0.01 to 0.1 parts of active and passive protective structure GO nanosheets, 5 to 10 parts of isophorone diisocyanate, 5 to 10 parts of polyether polyols and 20 to 40 parts of solvents; wherein the active and passive protective structure GO nanosheets are GO nanosheets grafted with hydroxybenzothiazole disulfide.

2. The polyurethane composite coating according to claim 1, characterized in that: The hydroxybenzothiazole disulfide is self-made, and its preparation process is as follows: (1) 0.01-0.1 mol of dibenzothiazole disulfide and 500-100 mL of chloroform are mixed, and then 0.01-0.1 mol of β-mercaptoethanol is added dropwise, and the mixture is reacted under stirring conditions. The reaction temperature of the stirring reaction is 20-30° C. and the stirring time is 3-4 hours; (2) After the reaction, hydroxybenzothiazole disulfide is obtained, extracted with a 3-5% by mass NaOH aqueous solution and deionized water, dried with Na2SO4 and filtered, and then purified by recrystallization with n-hexane after rotary evaporation to obtain the treated hydroxybenzothiazole disulfide.

3. The polyurethane composite coating according to claim 1, characterized in that: The coating comprises the following raw materials by weight: 0.02-0.06 parts of active and passive protective structure GO nanosheets, 6-9 parts of isophorone diisocyanate, 8-10 parts of polyether polyol and 28-32 parts of solvent.

4. The polyurethane composite coating according to claims 1 to 3, characterized in that: The preparation method of the active and passive protection structure GO nanosheet comprises the following steps: (1) mixing GO nanosheets and N,N-dimethylformamide and performing ultrasound to obtain a GO nanosheet mixed solution; (2) The GO nanosheet mixed solution is mixed with hydroxybenzothiazole disulfide and N,N-dimethylformamide, stirred, and then centrifuged, washed and dried to obtain active and passive protective structure GO nanosheets.

5. The polyurethane composite coating according to claim 4, characterized in that: In the step (1), the dosage ratio of GO nanosheets to N,N-dimethylformamide is 0.5-1 g: 100-300 mL, and the ultrasonication time is 30-40 min.

6. The polyurethane composite coating according to claim 5, characterized in that: The obtained GO nanosheet mixed solution is mixed with hydroxybenzothiazole disulfide and N,N-dimethylformamide, wherein the dosage ratio of the hydroxybenzothiazole disulfide and N,N-dimethylformamide is 0.5-1g:100-300mL; the stirring is carried out under stirring conditions, the stirring temperature is preferably 55-65°C, the stirring speed is 200-300rpm, and the stirring time is 5-6h; the centrifugation is centrifugal separation at 8000rpm for 10min; the washing is alternating washing with ethanol and deionized water.

7. The polyurethane composite coating according to any one of claims 1 to 3, characterized in that: The polyether polyol is one or more of NX9005, NX9006 or NX9007; the solvent is a mixed solution of toluene and N,N-dimethylformamide, with a mass ratio of 1-2g:1g.

8. A method for preparing a polyurethane composite coating according to any one of claims 1 to 7, characterized in that: The following steps are included: (1) mixing the active and passive protection structure GO nanosheets with isophorone diisocyanate and a solvent to obtain a mixed slurry; (2) adding polyether polyol to the mixed slurry to obtain a polyurethane composite slurry; (3) Spraying the polyurethane composite slurry onto the surface of a substrate and curing the slurry to obtain a polyurethane composite coating having anti-friction and anti-corrosion properties.

Citation Information

Patent Citations

  • 2-mercaptobenzothiazole-modified graphene oxide anticorrosive paint and preparation method thereof

    CN106700823A

  • Metal-based self-repairing coating as well as preparation method and application thereof

    CN109371451A

  • Preparation of silicone oil-containing lubricating anti-corrosion composite coating with low friction coefficient

    CN112266717A

  • Preparation method of graphene anticorrosive paint

    CN114907712A

  • Benzothiazole modified polyaspartate polyurea antifouling paint as well as preparation method and application thereof

    CN115418156A